Mental Health Symptoms in Literature since Modernism - Boileau, Nicolas Pierre. author. aut Link
X, 283 p.
Keywords: The Function of Symptoms in British Literature since Modernism looks at various ways of treating symptoms of psychological disorders in the literature of the long twentieth century. This book shows that literature can, in its questioning of commonly accepted views of this lived experience of psychic symptoms, help engender new theories about the functioning of subjective cases. Modernism emerged at about the same time as Freudian psychoanalysis did and the aim of this book is to also show that to a certain extent, Woolf preceded Freud in her exploration of the symptom and contributed to fashioning another approach that is now more common, especially in writers from the 1990s-onwards. Nicolas Pierre Boileau is Senior Lecturer at the Aix-Marseille University, France. Nicolas Pierre Boileau is Senior Lecturer at the Aix-Marseille University, France. Nicolas Pierre Boileau is Senior Lecturer at the Aix-Marseille University, France. Nicolas Pierre Boileau is Senior Lecturer at the Aix-Marseille University, France. Nicolas Pierre Boileau is Senior Lecturer at the Aix-Marseille University, France. Nicolas Pierre Boileau is Senior Lecturer at the Aix-Marseille University, France.